Affections of the salivary ducts in buffaloes - Misk, N.A. (Open Vet J, 2014)
The aim of the present study was to determine different affections of the salivary ducts in buffaloes with special reference to diagnosis and treatment. The study was carried out on 39 buffaloes suffering from different affections of the salivary ducts. The recorded affections of the salivary ducts in buffaloes include; ectasia of the parotid duct (21 cases), parotid duct fistula (15 cases) and sialocele (3 cases). Each case was subjected to full study including case history, clinical examination, diagnosis, and treatment whenever possible. Exploratory puncture and radiography were used for confirmation of diagnosis. Intraoral marsupialization was performed for treatment of parotid duct ectasia. Salivary fistula was corrected by one of two successful techniques; the first by reconstruction of the parotid duct and the second by ligation of the parotid duct just caudal to the fistula opening. Sialoceles were corrected by removal of the mandibular salivary gland of the affected side.